Republic of Korea : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
This 2002 Article IV Consultation highlights that the economic growth of Korea rose to about 6 percent in 2002 from 3 percent in 2001. Buoyant consumption and residential construction spending underpinned the recovery beginning in late 2001. In 2002, exports rebounded strongly in spite of a weaker-than-expected recovery in the global economy. Unemployment has eased to near pre-crisis levels, although wage rises have been matched by productivity growth. In terms of macroeconomic policies, the fiscal surplus was substantially higher than budgeted, resulting in a contractionary fiscal stance in 2002.